Stigma and depression among heterosexual men and women living with HIV in the UK: Investigating a conceptual framework - Ada R. Miltz; Janey Sewell; Fumiyo Nakagawa; Lorraine Sherr; Iain Reeves; Carole Kelly; Hannah Kitt; Valerie Delpech; Anu Fasanya; Alex Sparrowhawk; Vicky Lomas; Andrew Ustianowski; et al. (PLoS ONE, 2026)
Background Examining the relationship of HIV stigmatisation in different social settings with internalised HIV stigma, loneliness and depression among people with HIV, may help in further understanding HIV stigma and informing approaches and interventions to help to mitigate the impacts. The aim of this paper was to investigate among heterosexual men and women, a devised conceptual model of hypothesized causal connections between socio-demographic, HIV-related and psychosocial factors, measures of HIV stigmatisation, and depressive symptoms, in which feelings of loneliness because of HIV are theorised to mediate the relationship between internalised HIV stigma and depression. Methods and findings This was investigated using structural equation modelling (SEM) and data from Positive Voices, a national cross-sectional study of people living with HIV in the UK (2022−2023). The analysis is based on participants who identified as heterosexual and were cis-gender (N = 1232). The mean age was 52 years; 48.5% were Black African, and 39.0% of white ethnicity. Twenty percent of participants were diagnosed with HIV within the last decade (2014−2022). Overall, 51.6% and 35.2% agreed or strongly agreed with the statements ‘I am ashamed of my HIV status’ and ‘I have poor self-esteem because of my HIV status’ respectively; 57.9% (n = 713/1232) agreed/strongly agreed with either item and were classified as positive for internalised HIV stigma. For the measure of having felt isolated/lonely because of HIV, the prevalence of responding with ‘yes, in the last year’ or ‘yes, but not in the last year’ was 14.2% and 11.7% respectively. The prevalence of depressive symptoms was 18.6% (PHQ-9 score ≥10). The data were consistent with the devised conceptual model. Of the factors investigated to be directly associated with internalised HIV stigma, the largest Beta coefficient was for the association with HIV stigmatisation in healthcare (Beta = 0.600; p < 0.001). The second largest was for having felt scared to be in public places because of HIV in the last year (Beta = 0.271; p < 0.001), closely followed by HIV stigmatisation from family (Beta = 0.269; p < 0.001). Of the factors investigated to be directly associated with depression, the largest Beta coefficient was for the association with having felt isolated/lonely because of HIV (Beta = 0.492; p < 0.001). The second largest was for the inverse association with resilience (Beta = −0.288; p < 0.001), followed closely by financial hardship (Beta = 0.267; p < 0.001), having ‘told most people in my life that I have HIV’ (Beta = 0.267; p < 0.001), and the inverse association with supportive network (Beta = −0.202; p < 0.001). The largest Beta coefficient for direct effects was for the association between internalised HIV stigma and having felt isolated/lonely because of HIV (Beta = 0.842; p < 0.001). Internalised HIV stigma was associated with depression indirectly through having felt isolated/lonely because of HIV (indirect Beta = 0.415; p < 0.001). Conclusions Our findings add to existing literature by implicating a number of key factors that upon intervention may help prevent or attenuate symptoms of depression in people living with HIV, including reducing stigmatisation in healthcare, internalised HIV stigma, and loneliness/social isolation.